Effects of nitrogen fertilization on development, flowering, and mineral nutrition of potted Costus productus Gleason ex Maas - Merida, Daniela [UNESP]; Pivetta, Kathia Fernandes Lopes [UNESP]; Mazzini-Guedes, Renata Bachin; de Castro, Carlos Eduardo Ferreira; Purquerio, Luis Felipe Villani (Taylor & Francis, 2017)
Due to the lack of information on mineral nutrition of ornamental plants, especially tropical species, we aimed to evaluate the effects of nitrogen fertilization on development, flowering, and mineral nutrition of potted Costus productus. Plants were cultivated along 1 year under protection in Ubatuba, São Paulo State, Brazil, and submitted to five treatments that corresponded to increasing nitrogen doses (0.0, 1.2, 2.4, 3.6, and 4.8 g N plant−1). Evaluated plant variables were potted development, height, dry matter of aerial part, number of inflorescences, and nutritional status. Analysis of variance and linear and polynomial regressions were performed for definition of the best adjustments according to the combination of significance and greater determination coefficient. The nitrogen fertilization positively influenced development, flowering, and mineral nutrition of potted C. productus plants, and the dose of 4.8 g N plant−1 promoted best results.
Keywords: Costaceae; nutrition; ornamental plant; tropical flower; Zingiberales